Utilization and sustainability-factors of parents-initiated day care programs in urban low-income communities - Laurel, Josephine Gayl P. (College of Home Economics, University of the Philippines, 2014)
The presence of parent-initiated day care programs in low-income communities shows a lack of early childhood care and education services in the country in spite of the existing laws and policies on early childhood care and education. This study examines how these day care programs are being used, and reveals the factors that sustain these day care programs. In a series of interviews with three Parent-teachers, Day Care Visits, and Focus Group Discussions with thirty-six parents, the study identifies the functions, activities, challenges, and sustainability-factors of these parent-initiated day care programs in their communities. The functions that have surfaced are: As a means of a Preparatory Level (for the elementary level), As a means of Family and Parenting Intervention (family and parenting support), and As a means of Community Involvement (bastion against violence in the communities, channel for improving parenting skills and behavior, and livelihood training). The activities that the parents carry out for the day care programs are mostly Financial Contributions (monthly and voluntary monetary contributions) and Manual Contributions (volunteer parents for activities, classroom management, etc.). The challenges that the day care programs face include the Need for Material Resources (funding, sufficient equipment and materials, space, etc.) and the Need for Non-Material Resources (safety, supportive parents, supportive community, etc.). The study has attributed the sustainability-factors to the Accessibility (low-cost, proximity, etc.) and the Reputation of the Parent-teacher/ Day Care Program (quality of teaching and trusted early childhood care and education provider).